Case Report: Disseminated Nocardiosis Caused by Nocardia vulneris in a Patient With Macroglobulinemia - Qiu, Fulan; Ma, Zhiyi; Zhong, Rongrong; Huang, Haonan; Wang, Yuehua; Liu, Hui (Frontiers in Public Health, 2022)
A case of disseminated nocardiosis caused by Nocardia vulneris in a 61-year-old man with macroglobulinemia and presenting with fever, cough, shortness of breath and muscle pain is reported herein. The isolated Nocardia strain was resistant to ciprofloxacin, but susceptible to amikacin, gentamicin, tobramycin, linezolid, trimethoprim-sulfamethoxazole, amoxicillin/clavulanic, moxifloxacin, ceftriaxone, cefotaxim, imipenem. The patient was started on meropenem combinations with doxycycline treatment, followed by trimethoprim-sulfamethoxazole, and then he was switched to a combination treatment of linezolid, amikacin and trimethoprim-sulfamethoxazole. The patient recovered and his condition remained stable. Although infection by Nocardia vulneris is rare, clinicians should be aware of its diagnostic, in addition, the MIC value of the drug sensitivity test should be concerned when there is a wide choice of medicines, and the current case was treated successfully with linezolid, amikacin and trimethoprim-sulfamethoxazole. And for the disseminated cases which are diagnosed definitely should be treated with at least 12 months of antimicrobial therapy, bacteriological examination and antimicrobial susceptibility testing should be performed repeatedly.